Competition and gains from trade: A quantitative analysis of China between 1995 and 2004 - HSU, Wen-Tai (Institutional Knowledge at Singapore Management University, 2016)
This paper provides a quantitative analysis of gains from trade for China over the period of 1995-2004, which was when China's openness drastically improved. We decompose gains from trade in two ways. First, we disentangle pro-competitive effects from a traditional Ricardian effect. Second, we separate the effect due to tariff reductions from that due to reductions in non-tariff trade costs. Our quantitative analysis shows that the pro-competitive effects account for 25.4% of the total welfare gains from trade, whereas the allocative effciency alone accounts for 22.3%. We also find that tariff reductions account for about 31.6% of reductions of overall trade costs, whereas the associated relative contribution to overall gains is slightly larger at 39.6%. In our multi-sector analysis, we find that when a sectoral markup is higher in 1995, there tends to be a larger reduction in the respective sectoral trade cost between 1995 and 2004, a tendency that is generally welfare improving. One methodological advantage of this paper's quantitative framework is that its application is not constrained by industrial or product classifications, and so it can be applied to countries of any size.